2022
DOI: 10.3390/ani12060690
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Soybean Meal with Lactobacillus acidophilus Allows Greater Inclusion of Vegetable Protein in the Diet and Can Reduce Vibrionacea in the Intestine of the South American Catfish (Rhamdia quelen)

Abstract: The objective of this study was to evaluate the effect of diets containing different inclusion levels (0%, 7%, 14%, 21% and 28%) of soybean meal fermented by Lactobacillus acidophilus (SMFL) on the zootechnical performance and intestinal health of South American catfish juveniles (Rhamdia quelen). The experimental design was completely randomized with five treatments and four replications and lasted 56 days. Five isoproteic (39% crude protein) and isoenergetic (4300 kcal of gross energy kg−1) diets were formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…In line with previous studies in animal feed (e.g., Qian et al., 2018 ; de Oliveira et al., 2022 ), our findings indicated that Lactobacillus can help in the nutritional value of converted plant-based protein while lowering antinutrient content. By fermenting grain flour at 37°C for 24 h with L. acidophilus , phytic acid and polyphenol content may be lowered (Binita R, Khetarpaul et al., 1997), whereas Ojokoh et al.…”
Section: Resultssupporting
confidence: 92%
“…In line with previous studies in animal feed (e.g., Qian et al., 2018 ; de Oliveira et al., 2022 ), our findings indicated that Lactobacillus can help in the nutritional value of converted plant-based protein while lowering antinutrient content. By fermenting grain flour at 37°C for 24 h with L. acidophilus , phytic acid and polyphenol content may be lowered (Binita R, Khetarpaul et al., 1997), whereas Ojokoh et al.…”
Section: Resultssupporting
confidence: 92%
“…The amino acid compositions of the diets are shown in Table 5. Inclusion levels of fermented soybean meal were determined based on similar studies (Hassaan et al, 2015; De Oliveira et al, 2022; Wang et al, 2016). In addition to FSBM, the formulated diets contained fish meal, soybean meal as protein sources, and wheat flour and soy oil as energy sources.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that fermented soybean meal (FSBM) can partially replace fish meal in diets without compromising fish performance (Azarm & Lee, 2014; Barnes et al, 2015; Choi et al, 2019; He, Li, et al, 2020; He, Yu, et al, 2020; Ilham & Fotedar, 2016; Jiang et al, 2018; Lee et al, 2016; Liang et al, 2017; De Oliveira et al, 2022; Shiu et al, 2015; Sotoudeh et al, 2016; Wang et al, 2016, 2019; Wu et al, 2003; Yamamoto et al, 2010). In addition, FSBM can have beneficial effects on fish health, such as improvements in biochemical parameters (Novriadi et al, 2017), lipid metabolism, antioxidant response (Jiang et al, 2018; Li et al, 2020) and intestinal health (Li et al, 2019; Shiu et al, 2015; Sotoudeh et al, 2016; Wang et al, 2016, 2019; Yamamoto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some bioactive peptides produced during soybean meal fermentation possess antimicrobial properties. The addition of soybean meal fermented by Lactobacillus acidophilus to the diet of South American catfish can reduce the concentration of intestinal Vibriococcaceae (De Oliveira et al ., 2022). Replacing soybean meal with 6% fermented soybean meal can reduce the total amount of fungi and coliform bacteria in chicken jejunum, which can improve the growth performance of chickens (Chachaj et al ., 2019).…”
Section: Biological Activities Of Fermented Soybean Mealmentioning
confidence: 99%